2017
DOI: 10.18097/pbmc20176301027
|View full text |Cite
|
Sign up to set email alerts
|

Peptide drug cortexin inhibits brain caspase-8

Abstract: Cortexin, a drug containing hydrolyzed brain peptides, has long been used in clinics, but the mechanisms of its action remain obscure. We have hypothesized that cortexin-related neuroprotection is associated with the ability of the drug to inhibit brain proteases. Cortexin effectively inhibited brain caspase-8, while its effects on caspase-1, -3, -9, cathepsin B and calpain were much less pronounced or absent. In addition, we isolated a peptide fraction from cortexin holding all the inhibitory capacity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
(12 reference statements)
0
4
0
2
Order By: Relevance
“…Actovegin is a highly purified extract of calf's blood comprising a mixture of over 200 biologically active components [8] . The exact mechanism of action of these agents is uncertain and pleiotropic effects including neuroprotection, regulation of neuronal metabolism, and neurotrophic activity have been postulated [ 7 , 9 , 10 ]. Direct and indirect effects of the nootropics on the cerebrovasculature have been described and some studies have suggested beneficial effects in stroke recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actovegin is a highly purified extract of calf's blood comprising a mixture of over 200 biologically active components [8] . The exact mechanism of action of these agents is uncertain and pleiotropic effects including neuroprotection, regulation of neuronal metabolism, and neurotrophic activity have been postulated [ 7 , 9 , 10 ]. Direct and indirect effects of the nootropics on the cerebrovasculature have been described and some studies have suggested beneficial effects in stroke recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Actovegin has been utilized for similar neurological conditions for nearly 50 years [ 8 , 9 ] and is licensed for use in Russia, Eastern European and Asian countries [8] . Cortexin is predominantly prescribed in Russia, where it used to treat a range of acute and chronic neurological disorders including stroke and cognitive impairment [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cortexin has been shown to produce effective and tissue-specifi c inhibition of caspase-8 activity in the brain. As proteases of the caspase family perform one of the key functions in neuron death in neurodegeneration, inhibition of caspase-8 can be regarded as a potentially possible mechanism of the neuroprotective action of the drug in vivo [48].…”
Section: Mechanisms Of Nervous System Changes In Covid-19 Penetration...mentioning
confidence: 99%
“…В связи с тем, что протеазам семейства каспаз и кальпаина приписывают ключевую функцию в гибели нейронов при разных типах нейродегенерации, предположили, что среди пептидов кортексина могут находиться ингибиторы этих ферментов. Действительно, было показано [15], что кортексин эффективно и тканеспецифично ингибирует активность каспазы-8 головного мозга. Ингибирование каспаз-3, -8 и -9, а также катепсина В и кальпаина также отмечено, но оно было менее эффективным.…”
unclassified
“…обладала нейропротективными свойствами in vitro. Ингибирование каспазы-8 может быть рассмотрено как один из потенциально возможных механизмов нейропротективного действия препарата in vivo [15].…”
unclassified